Diagnosing peritoneal tuberculosis. (19th June 2013) - Clancy, C; Bokhari, Y; Neary, P M; Joyce, M
Abstract : A 37-year-old male healthcare worker presented to the medical assessment unit complaining of a 3-month history of lethargy, weight loss, night sweats and intermittent abdominal discomfort. On examination there was some dullness to percussion at the right lung base and decreased breath sounds. He had mild generalised tenderness in his abdomen. Blood tests were normal. Chest x-ray and CT of the thorax showed small bilateral pleural effusions with no other abnormality. CT of the abdomen and pelvis however, showed ascites with extensive thickening of the peritoneum and marked induration of the mesentery and omentum. Mantoux test was positive. Laparoscopy was undertaken to outrule intra-abdominal malignancy and confirmed the diagnosis of tuberculosis. Peritoneal wall biopsies were taken from which Mycobacterium was isolated confirming peritoneal tuberculosis. He was started on rifampicin, isoniazid, pyrazinamide and ethambutol and completed a 6-month course without further complications.